A rare case report: left-sided gall bladder without situs inversus viscerum - Agrawal, Shambhu Nath; Verma, Amit; Kedia, Sunil; Padegaonkar, Amol; Mahobia, Hari S. (International Surgery Journal, 2021)
Left-sided gall bladder without situs inversus viscerum is a rare clinical entity. A left-sided gall bladder is a rare congenital anomaly defined as a gall bladder attached to the lower surface of the left lateral segment of the liver, to the left of the inter-lobar fissure and round ligament. We reported our experience of one cases of left-sided gall bladder in a woman aged 45 years who underwent laparoscopic cholecystectomy for acute calculous cholecystitis. Left-sided gall bladder may provide an unusual surprise to the surgeons during laparoscopy as routine pre-operative studies may not always detect the anomaly. Awareness of the unpredictable confluence of the cystic duct into the common bile duct (CBD) and selective use of intraoperative cholangiography aid in the safe laparoscopic management of this unusual entity. One previous case reported had shown cystic duct opened into the common hepatic duct on its right side in a patient with left sided gall bladder.